Luxury tourism and stakeholder views - selected coastal cities of Croatia - Gržinić, Jasmina; Bobanović, Mieta (Oeconomica Jadertina, 2020)
Elite tourism appears in a number of selective forms of tourism (cultural, sports, etc.) and is therefore often conceptually defined differently (luxury, premium, high quality, specialised, alternative, transformative). Destinations that are oriented to added benefits for the client and the development of partnerships compete better in the market of elite tourism. In Croatian tourism, some destinations are called destinations of elite tourism. However, there are differences in the development of Croatian coastal destinations that strive for high quality tourism. The aim of this paper is to examine the attitudes of stakeholders of selected coastal cities on the level of development of elite tourism. The purpose of the research is to point out the necessary changes in the model of tourism development (due to the risk of negative externalities in the form of pollution, noise, congestion, difficulty of access to the destination, lack of ambience) which does not favour high paying tourists but directs them to other destinations. The attitudes of coastal destination stakeholders were examined using a combined data collection method (survey method and in-depth interview). The results of the research indicate the lack of balanced destination development in the tourist system. The assessors were the least unified about the destination offer variables regarding the value-added offer and service variable. The contribution of the paper is recommendations to the public and private sector, as well as to the local population in order to improve the segment of luxury offers and reflect on the implementation of global tourism initiatives.